Model systems control the movement of rolling stock on humps - Kozachenko, D. N. (Science and Transport Progress, 2010)
The structure of control system model of rolling stock movement for simulation of a process of braking-up and making-up of freight trains on hump yards is presented. The model is made on the basis of weighted directed graphs. The model can be used in computer simulators for switching foremen as well as in software complexes for estimation of plan and profile of hump yards.